55.8k views
3 votes
If you were going to solve this system by elimination by adding the two equations together, what would be a correct first step? 4x − 6y = 10 5x + 7y = −2

User Aemxdp
by
4.9k points

1 Answer

1 vote

Answer:

x = 1 and y = -1

The first step is multiply the first one with 7 and the second equation with 6 and add

Explanation:

Given the equations are 4x - 6y = 10 and 5x + 7y = -2

Now multiply the first one with 7 and the second equation with 6 and add

We get

28x - 42y = 70

30x + 42y = -12

-----------------------(+)

58x = 58

x = 1

Substitute this value in one of the equations we get y

4(1) -6y = 10

y = -1

User Terje
by
4.8k points